Citizens' attitudes towards democratic deliberation - Viegas, J. M. L.; Santos, S. (Portuguese Journal of Social Science, 2012)
The economic and social crises the Western democracies are currently experiencing have aggravated ideological polarisation and increased citizens' distrust of both politicians and political institutions. As a result, it has become increasingly difficult to obtain consensus just at the moment when it is most needed in order to put into effect those reforms the situation demands. It is in this context that studies of democratic deliberation gain new relevance and significance, particularly within parliaments, which are the places, par excellence, for political debate and consensus building. However, democratic deliberation requires more than just institutions, rules and regulations: it requires a political culture that is imbued with these principles and values, that is to say, it need citizens and political actors with positive attitudes towards the various dimensions of democratic deliberation. The results obtained here point in the general direction of support for the different aspects of deliberation, both in the attitudes of the citizens' and the deputies, indicating some very specific differences between each of them.